2022
DOI: 10.1002/cphc.202200261
|View full text |Cite
|
Sign up to set email alerts
|

Gold–Hydrogen Analogy in Small–Sized Hydrogen–Doped Gold Clusters Revisited

Abstract: The analogy between gold and hydrogen is a subject of long‐standing debate. In the present work, we examine the validity of the gold‐hydrogen analogy in a series of small‐sized H‐doped gold clusters, Aun−1H with n varying between 2 and 10 and also investigate its dependence on the cluster size. Keeping in mind the importance of the role of structures, we make use of the genetic algorithm coupled with a density functional theory based method to exhaustively search and identify the energetically low‐lying struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 67 publications
(174 reference statements)
1
4
0
Order By: Relevance
“…In order to more clearly compare the effect of H atoms doping on the clusters, the structure characteristics of bare M clusters can be referred to the previous reports. Most of Au n H structures in our results are consistent with those reported by Megha at n=2–5, 7, 8, but different isomers are derived at n=6 and 9 [44] . Here we only give optimized structures of M n H (M=Cu, Ag and Au; n =2–9) clusters.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In order to more clearly compare the effect of H atoms doping on the clusters, the structure characteristics of bare M clusters can be referred to the previous reports. Most of Au n H structures in our results are consistent with those reported by Megha at n=2–5, 7, 8, but different isomers are derived at n=6 and 9 [44] . Here we only give optimized structures of M n H (M=Cu, Ag and Au; n =2–9) clusters.…”
Section: Resultssupporting
confidence: 91%
“…Most of Au n H structures in our results are consistent with those reported by Megha at n = 2-5, 7, 8, but different isomers are derived at n = 6 and 9. [44] Here we only give optimized structures of M n H (M=Cu, Ag and Au; n = 2-9) clusters. For M 2 H, both the Cu 2 H and Au 2 H have tilted structures, while the Ag 2 H has a linear geometry where the H atom is inserted to two Ag atoms.…”
Section: Results and Discussion The Structural Features Of M N H (M=c...mentioning
confidence: 99%
“…Therefore, the H atom provides its 1s electron as a valence electron and behaves like a surrogate of the Au atom. Theoretical calculation by Ghanty and Banerjee demonstrated that the geometric and electronic structures of HAu n –1 ( n = 2–10, 20) are similar to those of pristine Au n . , Figure compares the geometric structures of the most stable isomers of Au n and HAu n –1 ( n = 2–10, 20). Both Au n and HAu n –1 ( n = 2–10) possess planar structures except HAu 9 .…”
Section: Gold–hydrogen Analogy In Naked Gold Superatomsmentioning
confidence: 97%
“…Most stable structures of Au n and HAu n –1 ( n = 2–10, and 20). Color code: yellow = Au; cyan = H. Reproduced with permission from refs and . Copyright 2016 American Chemical Society and Copyright 2022 Wiley-VCH GmbH.…”
Section: Gold–hydrogen Analogy In Naked Gold Superatomsmentioning
confidence: 99%
See 1 more Smart Citation